2017
DOI: 10.1111/oik.04890
|View full text |Cite
|
Sign up to set email alerts
|

Fear and lethality in snowshoe hares: the deadly effects of non‐consumptive predation risk

Abstract: Predators play a critical, top–down role in shaping ecosystems, driving prey population and community dynamics. Traditionally, studies of predator‐prey interactions have focused on direct effects of predators, namely the killing of prey. More recently, the non‐consumptive effects of predation risk are being appreciated; e.g. the ‘ecology of fear’. Prey responses to predation risk can be morphological, behavioural, and physiological, and are assumed to come at a cost to prey fitness. However, few studies have e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 55 publications
1
33
0
Order By: Relevance
“…The antipredator responses and their associated costs drive an evolutionary arms race between predator and prey, and constitute what is known as the "ecology of fear" (Brown et al, 1999), "degree of fear" (Stankowich and Blumstein, 2005), or "cost of fear" (Martin, 2011). The costs of anti-predator responses can include reduced survival (Dudeck et al, 2018;MacLeod et al, 2018); growth (Pangle et al, 2007); fecundity (Ruxton and Lima, 1997;Naidenko et al, 2003;Voznessenskaya et al, 2003;Fuelling and Halle, 2004;Creel et al, 2007) and reproduction (Zanette et al, 2011;Bonnington et al, 2013;Dudeck et al, 2018). More recently, limited evidence have shown that predation risk can drive an increase in current reproductive investment with associated costs to future reproduction (Duffield et al, 2017;Haapakoski et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The antipredator responses and their associated costs drive an evolutionary arms race between predator and prey, and constitute what is known as the "ecology of fear" (Brown et al, 1999), "degree of fear" (Stankowich and Blumstein, 2005), or "cost of fear" (Martin, 2011). The costs of anti-predator responses can include reduced survival (Dudeck et al, 2018;MacLeod et al, 2018); growth (Pangle et al, 2007); fecundity (Ruxton and Lima, 1997;Naidenko et al, 2003;Voznessenskaya et al, 2003;Fuelling and Halle, 2004;Creel et al, 2007) and reproduction (Zanette et al, 2011;Bonnington et al, 2013;Dudeck et al, 2018). More recently, limited evidence have shown that predation risk can drive an increase in current reproductive investment with associated costs to future reproduction (Duffield et al, 2017;Haapakoski et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…These are likely to be induced by continuous processes, such as predation intensity (including parasites), food web abundance, nesting availability, population density, climate variations, weather in its various forms, geomagnetic variations, and extraterrestrial fluxes such as ultraviolet radiation and cosmic rays. Recent work documents that just the fear of predation can also affect population reproduction and survival (Macleod et al, 2018). Some of these are local and some are more global in nature.…”
Section: Conceptual Modelmentioning
confidence: 99%
“…As part of the acute stress response, glucocorticoids promote energy mobilization by stimulating catabolic actions, modulate immune and inflammatory responses, and shutdown long‐term functions such as maintenance and reproduction to redirect energy towards emergency functions (Sapolsky et al, ; Wingfield et al, ). While essential to promote immediate survival, sustained or chronic activation of the stress response through high predator exposure may severely deter long‐term survival and reproduction (MacLeod, Krebs, Boonstra, & Sheriff, ; Sheriff et al, ), which can, in turn, impact population dynamics of prey species (Boonstra, Hik, Singleton, & Tinnikov, ).…”
Section: Introductionmentioning
confidence: 99%
“…The predation‐stress hypothesis is more recent and has consequently been less studied than the predation‐sensitive foraging hypothesis (Clinchy et al, ) . However, it is receiving growing empirical support (Clinchy et al, ; Hammerschlag et al, ; Yin, Yang, Shang, & Wei, ) and it seems to play a central role in the dramatic demographic fluctuations of the snowshoe hare Lepus americanus —lynx Lynx canadensis cycles (Boonstra et al, ; MacLeod et al, ; Sheriff et al, ). Still, in some systems, the predation‐stress hypothesis does not apply.…”
Section: Introductionmentioning
confidence: 99%